1985
DOI: 10.1002/ajpa.1330680110
|View full text |Cite
|
Sign up to set email alerts
|

Population distribution of the human vitamin D binding protein: Anthropological considerations

Abstract: The polymorphism of the serum vitamin D binding protein (DBP) in humans is based on the existence of three common alleles, Gc1F, Gc1S, and Gc2, and 84 rare alleles. The geographical distribution of Gc1F, Gc1S, and Gc2 alleles shows north to south clines, together with a balanced equilibrium between the Gc1F or Gc1S allele frequency and the Gc2 frequency. The distribution of the FST values shows high variability within a geographical area. For European and North Asiatic groups, the FST values are the lowest obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
37
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 53 publications
12
37
1
Order By: Relevance
“…Genome-wide association studies have shown that the polymorphism rs7041 and rs4588 are associated with circulating 25(OH)D 3 levels (6,302,475); TT carriers for rs7041 (Gc1S) and AA carriers for rs4588 (Gc2) are associated with lower 25(OH)D 3 levels. The prevalence of these polymorphisms differs between racial groups (97,132,219). Black and Asian populations are far more likely to carry the Gc1f form of DBP, while whites more frequently exhibit the Gc1s form of DBP.…”
Section: Dbpmentioning
confidence: 99%
“…Genome-wide association studies have shown that the polymorphism rs7041 and rs4588 are associated with circulating 25(OH)D 3 levels (6,302,475); TT carriers for rs7041 (Gc1S) and AA carriers for rs4588 (Gc2) are associated with lower 25(OH)D 3 levels. The prevalence of these polymorphisms differs between racial groups (97,132,219). Black and Asian populations are far more likely to carry the Gc1f form of DBP, while whites more frequently exhibit the Gc1s form of DBP.…”
Section: Dbpmentioning
confidence: 99%
“…The difference between Greeks and the other European populations is the lower GcIF and Gc2 and the higher Gcls al lele frequencies. The lower Gc2 frequency could be explained by the proposed corre lation of its frequency with different geo graphical factors [Papiha et al, 1982;Constans et al, 1985]. On the other hand to ex plain the geographical distribution of the Gcls and GcIF alleles further data are needed [Constanset al, 1985].…”
Section: Resultsmentioning
confidence: 99%
“…As for Mongoloid populations, such specific alleles are typically illustrated by the Di S antigen of the Diego blood group (Layrisse et al, 1955), the Gmab3st haplotype of immunoglobulin heavy chain allotypes (Gin, for review see Matsumoto, 1988), the TFDChi allele of transferrin (for review see Kamboh and Ferrell, 1987), a set of rare mutant alleles of vitamin D binding protein (DBP, initially called groupspecific component, Gc, for review see Constans et al, 1985), and so on. The distribution of the rare variants such as TFDChi or DBP variants informs us anthropological relationship between populations, their exchanges, and their migrations (Constans et al, 1985). Based on occurrence or absence of the BF*Fbl allele, Mongoloids could be divided into two groups, which findings implied that two core populations might have occurred before the differentiation of Mongoloid into various groups.…”
Section: Methodsmentioning
confidence: 99%
“…Analytical data on the Gm haplotype distribution among various Mongoloids provides an evidence for the occurrence of two distinct populations among paleo-Mongoloid populations of East Asia in the past (Matsumoto, 1988). In addition, Constans et al (1985) deduced from the distributions of seven rare variants at DBP locus that considerable differentiation among Mongoloid populations existed, especially between northern and southern ones during the migration to the Americas. Z2=14.5, p--0.…”
Section: Methodsmentioning
confidence: 99%